Analysis of nutritional status and needs of 15-18 year old high school students - Moh. Hasbi Assidiqi; Hendra Mashuri; I Komang Sukarata Adnyana (Universitas Sriwijaya, 2025)
Research Problems: Lack of understanding of the nutritional status and needs of high school students aged 15-18 years can impact their health and academic performance, so an in-depth analysis is needed to determine nutritional adequacy and the factors that influence it. Research Objectives: This study aims to analyse the status and nutritional needs of grade 10 students of SMAS Karya Wiata Singaraja. Methods: This type of research is a type of quantitative descriptive research using the survey method. Results: Based on the results of the research, the results of the status and nutritional needs of grade 10 students of SMAS Karya Wisata Singaraja were obtained, several students had not reached optimal nutritional status. Of the total 54 students studied, 5 people or about 9% of students had severe obesity nutritional status, while 32 people or around 59% of students had good/ideal nutritional status. In addition, 12 people or about 22% of students have a mild lean nutritional status, 2 people or about 4% of students have a severely emaciated nutritional status, and 3 people or about 6% of students have a mild obese nutritional status. As for macro nutritional needs, the average carbohydrate nutritional needs of students were 455.94 grams with a median of 455 grams, the highest value of 684 grams and the lowest value of 320 grams. The average protein requirement is 113.99 grams, with a median of 111 grams, the highest value of 171 grams and the lowest value of 80 grams. Then the average fat requirement was 84.43 grams with a median of 82 grams, the highest value of 127 grams and the lowest value of 59 grams. Conclusion: So that it was concluded that the nutritional status of grade 10 students of SMAS Karya Wisata Singaraja, showed that there were still some students who had not reached the optimal nutritional status and needed treatment from Physical Health and Education teachers and the parents of students.